Defining a non-eosinophilic inflammatory subtype in COPD: the role of CXCL9 and type 1 immune responses - Chengsheng, Yin; Jiacui, Song; Hasegawa, Takehiro; Yao, Ling; Kondo, Takami; Huiping, Li (Frontiers in Immunology, 2025)
BackgroundC–X–C motif chemokine ligand 9 (CXCL9) is induced by the interferon-γ response, and its receptor, C–X–C motif chemokine receptor 3, is a well-established marker of T-helper 1 (Th1) cells, which play an essential role in type 1 immune responses. CXCL9 expression is upregulated in patients with interstitial lung disease (ILD), COVID-19, and asthma. Although type 1 inflammation and CD8+ T cell activation are considered central to the inflammatory pathophysiology of chronic obstructive pulmonary disease (COPD), the relationship between blood levels of Th1 chemokines and this pathophysiology remains unclear. This study aimed to investigate the relationship between CXCL9 and chronic respiratory diseases.MethodsWe conducted a retrospective cohort study. The serum levels of CXCL9, surfactant protein A (SP-A), Krebs von den Lungen-6 (KL-6), and C-reactive protein (CRP) were analyzed in 165 patients with ILD and COPD. COPD was diagnosed using pulmonary function tests according to the Global Initiative for Chronic Obstructive Lung Disease criteria. Statistical analyses included Fisher’s exact test, Steel–Dwass test, Mann–Whitney U, and Wilcoxon test. An unsupervised hierarchical cluster analysis using complete linkage and Euclidean distance was performed for data clustering.ResultsCXCL9 levels were significantly higher in patients with COPD and interstitial ILD than in healthy smokers and non-smokers. The median serum CXCL9 levels in patients with ILD, COPD, healthy smokers, and healthy nonsmokers were 61.6, 69.3, 37.0, and 32.5pg/mL, respectively. CXCL9 levels in patients with COPD significantly correlated with KL-6, SP-A, blood eosinophil ratio, lactate dehydrogenase (LDH), and CRP levels, with correlation coefficients of 0.243, 0.381, 0.225, 0.369, and 0.293, respectively. Additionally, CXCL9 levels were negatively correlated with FEV1%. Levels of LDH and KL-6 and the neutrophil ratio were significantly elevated in non-eosinophilic COPD patients with high CXCL9 levels.ConclusionsOur results highlight the potential role of CXCL9 in the inflammatory pathophysiology of COPD.